1970
DOI: 10.33899/edusj.1970.58954
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenylchroman-4-one as Synthone in Synthesis of New Five and Six Membered Rings Heterocyclic Compounds

Abstract: Chroman-4-one derivatives 1(a-i) were prepared by Pechman condensation of phenol or its substitutions with cinnamic acid by using polyphosphoric acid. These derivatives were reacted with hydrazine hydrate in refluxing ethanol to yield pyrazoline derivatives (2). The utility

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The alternative structure 43 would not be expected to show downfield shift of such a magnitude. Raoof et al (2011) reported the synthesis of a few five membered (pyrazoles) and six membered heterocycles (pyrimidin-2-ones) from 3-arylidene-4-flavanones. [46] Heating a solution of (Z)-3-arylideneflavanones 22 in presence of urea in EtOH afforded the 4-(2-chlorophenyl)-5-phenyl-3,4,4a,5-substitutedchromano-[4,3-d] pyrimidin-2-ones 44 in low yields (Scheme 13).…”
Section: Rigid Flavone Analoguesmentioning
confidence: 99%
See 1 more Smart Citation
“…The alternative structure 43 would not be expected to show downfield shift of such a magnitude. Raoof et al (2011) reported the synthesis of a few five membered (pyrazoles) and six membered heterocycles (pyrimidin-2-ones) from 3-arylidene-4-flavanones. [46] Heating a solution of (Z)-3-arylideneflavanones 22 in presence of urea in EtOH afforded the 4-(2-chlorophenyl)-5-phenyl-3,4,4a,5-substitutedchromano-[4,3-d] pyrimidin-2-ones 44 in low yields (Scheme 13).…”
Section: Rigid Flavone Analoguesmentioning
confidence: 99%
“…Raoof et al (2011) reported the synthesis of a few five membered (pyrazoles) and six membered heterocycles (pyrimidin-2-ones) from 3-arylidene-4-flavanones. [46] Heating a solution of (Z)-3-arylideneflavanones 22 in presence of urea in EtOH afforded the 4-(2-chlorophenyl)-5-phenyl-3,4,4a,5-substitutedchromano-[4,3-d] pyrimidin-2-ones 44 in low yields (Scheme 13). Although the structure of the pyrimidines 44 (with three consecutive chiral centres) was assigned by UV, IR and NMR spectral studies, but the relative stereochemistry is not described.…”
Section: Rigid Flavone Analoguesmentioning
confidence: 99%